Study protocol: behaviour change intervention to promote healthy diet and physical activity in overweight/obese adults with diabetes attending health care facilities in Muscat: a cluster rendomised control trial - Thamra Al Ghafri; Huda Anwar; Eiman Al Hinai; Thuraya Al Harthi; Fathiya Al Jufaili; Reyadh Al Siyabi; Shamsa Al Harthi; Said Al Hasani; Mohammed Al Harthi; Saud Al Harthi (BMC, 2021)
Abstract Background Healthy behavior is an essential component in type 2 diabetes (T2D) management. Promoting healthy lifestyle is one of the priorities of primary health care in Oman. This study aims to evaluate the effectiveness of a multi-component intervention in promoting physical activity (PA) and healthy diet and its implications on body mass index and glycemic control in adults with diabetes attending primary care. Methods A one year 1:1 cluster randomized controlled trial will be utilized to compare the use of phone consultations, a multi component interactive phone application and pedometers with the usual diabetes care on promoting PA and healthy diet. Participants will be screened for inactivity and should be T2D, aged18-65 years, and overweight or obese. Eight primary centers will be randomly selected in each arm (n = 375). The primary outcome is the between arms differences in PA and diet scores, BMI and HbA1c over 12 months from baseline. Additionally, secondary outcomes will include cardiovascular outcomes (BP, and lipids). The trial has received ethical approval from the Omani Research and Ethical Review and Approval Committee. All eligible participants will be invited to their respected health centers to provide informed consent. Discussion This study will contribute to the integration of healthy lifestyle approach using artificial intelligence to primary diabetes care. Results from this study will be disseminated through workshops, policy briefs, and peer-reviewed publications, local and international conferences. Trial registration Trial registration number ISRCTN71889430 . Date applied: 28/11/2020. Date assigned: 01/12/2020.